(untitled) (Medical Forum Monthly, 2024)
Background: Enteric fever (Typhoid fever) is widely recognized as a major public health problem in developing countries. Objective: To evaluate the treatment outcome of enteric fever in children Study Design: Retrospective descriptive study. Place and Duration of Study: This study was conducted at the Paediatric department, Ghulam Muhammad Mahar Medical College Hospital Sukkur from January 2009 to December 2011. Patients and Methods: This was a retrospective study, included all patients of enteric fever, of both sex and age ranged from 6m to 13 years. All enteric patients were confirmed by serological test Typhidot IgM or IgM and IgG positive .The data was collected from case record for demography and treatment out come. Results: A total of 360 patients were diagnosed to have enteric fever during this period. Mean age of presentation was 6.47 years and 166 (46.12%) patients were <5 years whereas 194 (53.88%) were > 5 years of age. Male:Female ratio was 2:1. Serological test typhidot IgM was positive in 290 (80.5%) and both (IgM + IgG) were positive in 70 (19 45%) of cases. Raised ALT was seen in 90(25%) of cases. Complications were seen in 52 (14.4%) of cases, hepatitis 10 (2.77%), hepatic abscess 3 (0.83%) intestinal hemorrhage 8 (2.22%), peritonitis 4 (1.11%) intestinal perforation 4 ( 1.11%), cholecystitis 6 (1.66%), paralytic ileus 3 (0.83%) enteric encephalopathy 3 (0.83%), meningitis1(0.27%) osteomyelitis 3 ( 0.83%), septic arthritis 2 (0.55%) pancytopenia 3 (0.83%), pneumonia 1 (0.27%) and renal abscess 1(0.27%). Two patients expired (0.55%), one was enteric encephalopathy and other intestinal perforation with peritonitis. Conclusion: Enteric fever remains a major cause of morbidity and mortality in our part of country. Major complications found in our cases were hepatitis, hepatic abscess, intestinal hemorrhage, intestinal perforation, peritonitis, cholecystitis, enteric encephalopathy, meningitis, osteomyelitis, septic arthritis.